The effect of beneficial microorganism as biofertilizer application in hydroponic-grown tomato - Setiawati, Mieke Rochimi; Afrilandha, Nandha; Hindersah, Reginawanti; Suryatmana, Pujawati; Fitriatin, Betty Natalie; Kamaluddin, Nadia Nuraniya (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2023)
The use of N2-fixing bacteria and growth hormone-producing rhizobacteria delivers nitrogen, enhances nutrients absorption by plants, and reduces the usage of inorganic fertilizers. Implementing biofertilizer in the hydroponic system as a means to reduce application of synthetic nutrient is recently in interest due to economic, food safety, and sustainability factors. This study determines the effects of biofertilizer dose on tomato yields in the hydroponics system. A randomized block design was utilized that consisted of seven treatments, namely 100% inorganic fertilizer and 0% biofertilizer (control), and various doses of inorganic nutrient combined with 25%, 50%, 75%, and 100% biofertilizer. The result illustrated that the application of biofertilizer augmented the population of endophytic bacteria, Azotobacter sp., Azospirillum sp., phosphate solubilizing bacteria, and nitrogen content. The distinct combination of biofertilizer did not alter the phosphorus and potassium content compared to control samples however resulted in superior tomato grade. The 50% inorganic fertilizer and 100% biofertilizer combination amplified the weight of the fruit by 36% compared to the control. This finding indicates that the application of biofertilizers in the hydroponic system for tomato plants is not only beneficial in minimizing the dosage of inorganic fertilizers but also enhancing the fruit quality.